Pengelolaan Kegiatan Agama dan Moral Di Taman Kanak-Kanak Telkom Schools Padang - Atika, Rahmi Sri; Wirman, Asdi (Indonesian Journal of Islamic Early Childhood Education, 2019)
This study aims to describe how the management of religious and moral activities at the Padang Schools TK. The method used by the researcher in this research is descriptive method with a qualitative approach. Data collection techniques by means of observation, interviews and documentation. The analysis technique carried out is data triangulation. The results of the study at Padang TK TK Schools, that the religious and moral activities at the Padang Telkom Schools TK had been carried out in accordance with the planned plans. Activities carried out such as shaking children, pledging and praying, ablution, reading the Asmaul Husna, short letters, prayer, humming al-Quran, tahfidz, reading prayers before washing hands and eating, reading prayers after eating, and reading daily prayers before going home school. Furthermore, after the child has carried out the activities the teacher conducts an evaluation by means of daily assessment, weekly assessment, and final semester assessment.